Epistemology of Knowledge: Bridging Western and Islamic Thought - Refinal; Mahyudin Ritonga; Rusydi; Riki Saputra (Walidem Institute and Publishing, 2025)
Objective: This study aims to examine the epistemology of knowledge by bridging Western and Islamic thought, and analyze the potential integration of these perspectives in the development of knowledge. The main objective of this research is to understand how epistemology is viewed within the contexts of Western and Islamic thought and explore the possibility of a more holistic integration between them. Theoretical Framework: The theoretical framework of this research is based on classical Western epistemology, which emphasizes reason and empiricism, compared to Islamic epistemology which emphasizes revelation, intellect, and experience in understanding truth. These two theories are analyzed to identify fundamental similarities and differences in the formation of knowledge. Literature Review: The literature review covers studies on epistemology in Western philosophy, including thinkers such as Descartes, Kant, and Dewey, as well as epistemological perspectives in Islamic tradition through the thoughts of Al-Ghazali, Ibn Sina, and Al-Farabi. The review also examines recent studies on the dialogue between Western and Islamic knowledge systems, focusing on efforts to integrate these two systems of knowledge. Methods: The research method used is a qualitative approach with a comparative analysis. Data is collected through literature studies that discuss Western and Islamic epistemological perspectives, as well as previous research relevant to the theme of this study. Results: The results of the study show that there are fundamental similarities in the pursuit of knowledge between the two perspectives, although there are differences in reasoning approaches and ontological foundations. Implications: The implications of this research highlight the need for an interdisciplinary approach in education and the development of knowledge that accommodates both perspectives. Novelty: The novelty of this research lies in the development of the concept of integrating Western and Islamic epistemology, which has not been widely explored in previous studies.